Network Analysis Applied to Post-concussion Symptoms in Two Mild Traumatic Brain Injury Samples - Faulkner, Josh W; Theadom, Alice; Snell, Deborah L; Williams, Matt N (Frontiers Media SA, 2023)
Objective: A latent disease explanation cannot exclusively explain post-concussion symptoms after mild traumatic brain injury (mTBI). Network analysis offers an alternative form of explanation for relationships between symptoms. The study aimed to apply network analysis to post-concussion symptoms in two different mTBI cohorts; an acute treatment-seeking sample and a sample 10 years post-mTBI. Method: The treatment-seeking sample (n = 258) were on average 6 weeks post-injury; the 10 year post mTBI sample (n = 193) was derived from a population-based incidence and outcomes study (BIONIC). Network analysis was completed on post-concussion symptoms measured using the Rivermead Post-Concussion Questionnaire. Results: In the treatment-seeking sample, frustration, blurred vision, and concentration difficulties were central to the network. These symptoms remained central in the 10 year post mTBI sample. A Network Comparison Test revealed evidence of a difference in network structure across the two samples (p = 0.045). However, the only symptoms that showed significant differences in strength centrality across samples were irritability and restlessness. Conclusion: The current findings suggest that frustration, blurred vision and concentration difficulties may have an influential role in the experience and maintenance of post-concussion symptoms. The impact of these symptoms may remain stable over time. Targeting and prioritising the management of these symptoms may be beneficial for mTBI rehabilitation.
Keywords: 5203 Clinical and Health Psychology; 52 Psychology; Neurosciences; Traumatic Head and Spine Injury; Brain Disorders; Clinical Research; Physical Injury - Accidents and Adverse Effects; Traumatic Brain Injury (TBI); Mental health; 1103 Clinical Sciences; 1109 Neurosciences; 1701 Psychology; 3202 Clinical sciences; 3209 Neurosciences; 5202 Biological psychology